An Artificial Intelligent-Based Chatbot for Dosage Prediction of Medicine Using Noval Deep Reinforcement Learning with Natural Language Processing - B, Phani Raghava; Ashok Kumar, S. (ECS transactions, 2022)
The aim is to create an artificial conversation entity (chatbot) using Python to predict dosage of medicine for healthcare treatments. Materials and Methods: Two algorithms, deep reinforcement algorithms, are compared with deep learning algorithm sample size taken 28. G power of 80% and sample size is calculated using G power tool. Results and Discussion: Performances of the score model validated test set accuracy with 95% confidence interval for deep reinforcement algorithm with different sub-samples having different number of intents comparing with deep learning, which has 85% accuracy. Conclusion: From the results, it is concluded that proposed algorithm deep reinforcement will produce better results than the existing algorithm.